PERLINDUNGAN HUKUM PIHAK KETIGA SEBAGAI PEMBERI JAMINAN HAK TANGGUNGAN TERHADAP PENGALIHAN PIUTANG SECARA CESSIE OLEH KREDITURDALAM HAL DEBITUR GAGAL BAYAR - Sihombing, Jelita; Sahril, Iran; Martien, Dhoni (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The credit agreement is a main agreement that can be followed by additional agreements. If the debtor defaults, the creditor can settle by transferring the receivables by Cessie. Credit agreements often occur where the debtor borrows collateral belonging to another person or third party in the form of a land certificate and then that person acts as the provider of mortgage rights to guarantee repayment of the debtor's debt. The involvement of a third party in a guarantee agreement often results in losses if the debtor fails to pay. The problem in this research is how to transfer receivables in Cessie by the creditor in the event that the debtor fails to pay against third party mortgage guarantees and what form of legal protection exists for third parties as providers of mortgage rights regarding the transfer of receivables in Cessie by creditors in the event that the debtor fails to pay. The theories used in this research are legal protection theory and contract theory.From the research results, the transfer of receivables by Cessie by the creditor in the event that the debtor fails to pay the third party mortgage guarantee does not comply with the applicable provisions as regulated in Article 613 of the Civil Code and Law of the Republic of Indonesia Number 4 of 1996 concerning Mortgage Rights. Form legal protection for third parties by filing a lawsuit before or during the execution process. The government, stakeholders and related parties are expected to make changes to Law of the Republic of Indonesia Number 4 of 1996 concerning Mortgage Rights over Land and Objects related to Land, by accommodating third party protection which is explicitly regulated in guaranteeing rights to land, these regulations do not clearly regulate the rights and obligations of third parties so they cannot provide legal protection for collateral owners.